2016
DOI: 10.1037/neu0000245
|View full text |Cite
|
Sign up to set email alerts
|

Factor structure of cognition and functional capacity in two studies of schizophrenia and bipolar disorder: Implications for genomic studies.

Abstract: Objective Impairments in cognition and everyday functioning are common in schizophrenia and bipolar disorder. Based on two studies of schizophrenia (SCZ) and bipolar I disorder (BPI) with similar methods, this paper presents factor analyses of cognitive and functional capacity (FC) measures. The overall goal of these analyses was to determine whether performance-based assessments should be examined individually, or aggregated on the basis of the correlational structure of the tests and as well as to evaluate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 37 publications
3
22
0
Order By: Relevance
“…That the cross-diagnostic cluster-solution was replicated using only a general cognitive factor as a clustering variable, suggests that a 'g' factor can be examined with some confidence in empirical clustering studies in even larger, 'messier' datasets that comprise different cognitive batteries. This has obvious implications for the genomic analyses of large-scale datasets focused on intra-individual differences in cognition in BD and SZ (Harvey et al, 2016, Harvey et al, 2014, and studies measuring the overlap between cognition and risk for psychiatric disease more broadly (Lencz et al, 2014, Hatzimanolis et al, 2015, Hill et al, 2016, Gale et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…That the cross-diagnostic cluster-solution was replicated using only a general cognitive factor as a clustering variable, suggests that a 'g' factor can be examined with some confidence in empirical clustering studies in even larger, 'messier' datasets that comprise different cognitive batteries. This has obvious implications for the genomic analyses of large-scale datasets focused on intra-individual differences in cognition in BD and SZ (Harvey et al, 2016, Harvey et al, 2014, and studies measuring the overlap between cognition and risk for psychiatric disease more broadly (Lencz et al, 2014, Hatzimanolis et al, 2015, Hill et al, 2016, Gale et al, 2008.…”
Section: Discussionmentioning
confidence: 99%
“…This was followed by post hoc pairwise voxel-wise comparisons across groups. Analysis 2: association between cognitive performance and brain structure Given the large body of evidence of one or two factors explaining the majority of the variance in cognitive function in healthy subjects [40][41][42][43] as well as in individuals with schizophrenia and BD [21,22], we chose to perform principal component analysis (PCA) as a data reduction step to reduce multiple comparisons. We then used a general linear model to assess whether the principal component factor scores were associated with cortical thickness and/or FA, controlling for sex, age, and parental education in all participants collapsed together, as well as separately within each diagnosis.…”
Section: Statistical Analysis Analysis 1: Cortical Thickness and Whitmentioning
confidence: 99%
“…Therefore, the relationships among brain structure, cognitive performance, serious mental illness, and aging require further disentanglement. Cognitive variability has been shown to be captured by a single factor in both schizophrenia and BD [21,22]. There also remains some debate regarding altered neurodevelopmental versus (early) neurodegenerative trajectories of the major psychoses (i.e., "an early hit" versus an accelerated aging mechanism), especially in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%
“…Genetic variance is one such mechanism and it is well established that certain genes predispose patients to cognitive impairment 7 . The heritability range varies in different domains in patients with schizophrenia, including working memory (0.3-0.6), executive function (0.3-0.6), episodic memory (0.3-0.6), and attention (0.54) 8 . Additional evidence has indicated that cognitive impairment often occurs in unaffected relatives of patients with schizophrenia 9,10 .…”
Section: Introductionmentioning
confidence: 99%